1996
DOI: 10.1002/(sici)1097-0274(199603)29:3<227::aid-ajim2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of cancer among benzene-exposed workers in China: Overall results

Abstract: A large cohort study of 74,828 benzene‐exposed and 35,805 unexposed workers employed between 1972 and 1987 in 12 cities in China were followed to determine mortality from all causes and the incidence of lymphohematopoietic malignancies and other hematologic disorders. Benzene‐exposed study subjects were employed in a variety of occupations, including painting, printing, and the manufacture of footwear, paint, and other chemicals. All‐cause mortality was similar in the benzene‐exposed and unexposed comparison g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
2
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(82 citation statements)
references
References 5 publications
5
70
2
3
Order By: Relevance
“…The authors also note that the confidence intervals are fairly wide despite the size and duration of follow-up of the study. Lamm et al 195 conducted a pooled summary analysis of 21 nonpetroleum industry studies, including data from an earlier follow-up of the Chinese cohort, 196 that evaluated the association between benzene exposure and risk of NHL. No significant association was reported in the overall analysis (OR 5 1.04, 95% CI: 0.94-1.14) or the analysis that excluded studies with multiple chemical exposures (OR 5 0.96, 95% CI: 0.86-1.06).…”
Section: Occupational and Environmental Chemical Exposuresupporting
confidence: 54%
See 1 more Smart Citation
“…The authors also note that the confidence intervals are fairly wide despite the size and duration of follow-up of the study. Lamm et al 195 conducted a pooled summary analysis of 21 nonpetroleum industry studies, including data from an earlier follow-up of the Chinese cohort, 196 that evaluated the association between benzene exposure and risk of NHL. No significant association was reported in the overall analysis (OR 5 1.04, 95% CI: 0.94-1.14) or the analysis that excluded studies with multiple chemical exposures (OR 5 0.96, 95% CI: 0.86-1.06).…”
Section: Occupational and Environmental Chemical Exposuresupporting
confidence: 54%
“…Parodi et al 197 examined the relative risk of NHL in an Italian municipality with close residential proximity to a coke oven, an industrial source of environmental benzene, and reported significant positive associations among men (RR compared to controls in Cornigliano [a district in Genoa] 5 2.4, 95% CI: 1.4-4.1; RR compared to controls in Genoa 5 1.7, 95% CI: 1.2-2.6), but not women (RR with Cornigliano controls 5 1.2, 95% CI: 0.6-2.5; RR with Genoa controls 5 1.0, 95% CI: 0.6-1.7). Overall, the epidemiologic evidence does not support a causal association between benzene exposure and NHL, as individual cohort and case-control studies have been inconsistent, with relative risk estimates above 21,[31][32][33]170,194,196,198,199 and below 31,176,191,[200][201][202] 1.0, and nonsignificant findings from pooled analyses ranging between 0.90 and 1.31. 191,195 Numerous studies examined the relation between solvent exposure and risk of NHL.…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 99%
“…Yin reported that total WBC reduced similarly in workers exposed to benzene (41). Therefore, in some countries, even lower levels have been adopted (0.5 ppm in Sweden) (42).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous environmental exposures have been associated with the development of MDS including tobacco [6] and alcohol use [7], infections [8], or auto-immune disorders [9]; however, the classic example linking an environmental toxin exposure to MDS development is highlighted from the observational case control studies involving benzene, an aromatic hydrocarbon and organic solvent derived from petroleumrefining, used in many occupational compounds [25]. The association, first described in Turkish shoe workers who developed bone marrow failure/pancytopenia states, [26] lead to further prospective cohort studies involving 74,828 benzene exposed subjects in China and revealed a significantly increased relative risk of MDS development approaching infinity [2]. The potential mechanisms of MDS development in benzene-exposed individuals have been described in two contexts: genotoxic and non-genotoxic.…”
Section: Cellular Damage: Toxic Environmental Exposures and Cellular mentioning
confidence: 99%
“…The median age at presentation approaches 70 with a slight male predominance of unknown clinical significance. Traditionally, MDS is characterized as either primary (idiopathic) or secondary with exposure to benzene [2], occupational chemicals [3], or prior treatment with radiation [4] or chemotherapy agents [5] well documented secondary causes. Additional data implicates exposure to tobacco [6], excessive alcohol [7], viral infections [8], or autoimmune disorders [9] as potential associations with MDS.…”
Section: Introductionmentioning
confidence: 99%